2022
DOI: 10.3389/fphys.2022.998665
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences during a cold-stress test in normobaric and hypobaric hypoxia: A randomized controlled crossover study

Abstract: Cold and hypoxia are two stressors that are frequently combined and investigated in the scientific literature. Despite the growing literature regarding normobaric hypoxia (NH) and hypobaric hypoxia (HH), responses between females and males are less often evaluated. Therefore, this study aims to investigate the physiological sex differences following a cold-stress test under normoxia, normobaric- and hypobaric hypoxia. A total of n = 10 females (24.8 ± 5.1 years) and n = 10 males (30.3 ± 6.3 years) from a unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
3
1
Order By: Relevance
“…Though accounting for a small percentage of SpO 2 , these results are consistent with Archiza et al (2020) findings regarding sex differences in diaphragmatic muscle fatigue under acute hypoxia. However, our finding of lower SpO 2 for females is inconsistent with prior work using less severe altitudes that found no sex differences ( Hohenauer et al, 2022 ; Karayigit et al, 2022 ). The altitudes examined here most closely align with the 8% O 2 used by Archiza et al (2020) .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Though accounting for a small percentage of SpO 2 , these results are consistent with Archiza et al (2020) findings regarding sex differences in diaphragmatic muscle fatigue under acute hypoxia. However, our finding of lower SpO 2 for females is inconsistent with prior work using less severe altitudes that found no sex differences ( Hohenauer et al, 2022 ; Karayigit et al, 2022 ). The altitudes examined here most closely align with the 8% O 2 used by Archiza et al (2020) .…”
Section: Discussioncontrasting
confidence: 99%
“…The altitudes examined here most closely align with the 8% O 2 used by Archiza et al (2020) . Moreover, given the small sample sizes used in previous work ( Hohenauer et al, 2022 ; Karayigit et al, 2022 ), their null result for sex differences in SpO 2 was possibly due to inadequate power. The larger sample size used in our study afforded us a better opportunity to assess these differences, and our results did indicate that the effect was quite small with sex, age, and BMI only accounting for 6% variance in SpO 2 ( Table 3 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, Vento et al (2022) identified markedly diminished capillary oxygenation levels and an increased occurrence of headache in females compared to males during acute hypoxia [28]. Despite the existence of studies that didn't observe sex differences [29,30], the inconsistence outcomes underpin the significance of investigating female responses to hypoxic stimuli. Therefore, our study aimed to compare the acute physiological effects after a single session of muscle damaging exercise, carried out under hypoxia (HYP) and normoxia (CON), and to evaluate the effects on subjective and objective recovery during a 72-hrs follow-up period.…”
Section: Introductionmentioning
confidence: 99%